2017
DOI: 10.1080/14735903.2017.1372850
|View full text |Cite
|
Sign up to set email alerts
|

Perennial grain crops in the West Soudanian Savanna of Mali: perspectives from agroecology and gendered spaces

Abstract: Perennial grain crops may play an important role in environmentally sound and socially just food systems for Africa. We study the future possibility of integrating perennial grains into Malian farming systems from the perspective of agroecology, and more specifically using a gendered space approach. We interviewed 72 farmers across the sorghum-growing region of Mali. We found that perennial grains offer a vision for transforming human relations with nature that mirrors the resource sharing of customary land te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Uneven maturation, which poses challenges in large-scale mechanized agriculture, may be viewed differently by smallholders since this implies that labor needs for harvesting get distributed over time. In their study in Mali, Rogé et al (2017) however found that both men and women highlighted reduced labor requirements as the most important benefit when discussing the idea of growing perennial sorghum. Peter et al (2017:288) meanwhile are referring specifically to African smallholder contexts when they argue that perennial grains should mainly be promoted in "locations where labor constraints reduce agricultural system efficiency."…”
Section: What Characterizes Smallholder Farming Systems and What Arementioning
confidence: 93%
See 3 more Smart Citations
“…Uneven maturation, which poses challenges in large-scale mechanized agriculture, may be viewed differently by smallholders since this implies that labor needs for harvesting get distributed over time. In their study in Mali, Rogé et al (2017) however found that both men and women highlighted reduced labor requirements as the most important benefit when discussing the idea of growing perennial sorghum. Peter et al (2017:288) meanwhile are referring specifically to African smallholder contexts when they argue that perennial grains should mainly be promoted in "locations where labor constraints reduce agricultural system efficiency."…”
Section: What Characterizes Smallholder Farming Systems and What Arementioning
confidence: 93%
“…Decreasing farm sizes may furthermore render farms too small for investments in lower-yielding and less flexible land uses, in contrast to settings where farmers may have "marginal" portions of large landholdings. That said, in a study set in a sorghum-growing region of Mali, Rogé et al (2017) find perennial grains to be highly compatible with existing customary land tenure relations and the resourcesharing logic of existing land use.…”
Section: What Characterizes Smallholder Farming Systems and What Arementioning
confidence: 98%
See 2 more Smart Citations
“…A study examining the concept of coproduction of knowledge analyzed how small farmers know, perceive, share, and apply knowledge of a changing climate and which resources they access for agroecological methods in this context [27]. In Mali [28], the cultivation of perennial cereals has allowed farmers to spend less on seeds. Food security improvements could be an important instrument in increasing female farmer's access to land and to natural resources, as well as improving soil quality, reducing labor at the beginning of the rainy season, and yielding more resources from uncultivated land.…”
Section: Africa and Agroecologymentioning
confidence: 99%